Diagnóstico y diseño estructural de la red alma mater a partir de un proceso participativo desde sus principales actores (2010)
The research project hereunto presented portrays the insight obtained from the intervention process carried out on Red Alma Mater. Said intervention process aimed at improving the organization's processes in general and the common level of awareness of actors' roles and relevance of their duties as team member. Furthermore, this intervention process relied on Red Alma Mater actors' active participation as its main strategy so as to diagnose its state of the art; thence, a new organizational structure design is thought of and implemented, and an ulterior first approach to impact measure on its current state of the art is thereby amounted.